WEB BASED MARKETING MANAGEMENT INFORMATION SYSTEMS (Study at CV. Karya Gaja Mandiri) - Aditya, Brahma Prananta (Jurnal Administrasi Bisnis, 2014)
The purpose of this study was to produce an accurate of information source, the right to also effectively and efficiently in carrying out marketing management in accordance with technological developments. This research method is qualitative research with descriptive approach. The focus of this research is to understand the overview of web-based marketing information systems and understand the overview of web-based marketing information system in support of marketing management that applied at CV. Karya Gaja Mandiri. Marketing information systems is become important thing for company in solving the marketing issues and analyzing the ways of company in competing with the others competitors, therefore the company can survive in the business competition. The results of this study are indicate several ways in marketing the product by online media using technique SEO (Search Engine Optimization) in attracting visitors online media and using DSS (Decision Support Systems) in planning the marketing strategies to create marketing activities can be run effectively and efficiently. Keywords: Marketing Information Systems, Marketing Management, Website ABSTRAK Tujuan dilakukannya penelitian ini adalah untuk menghasilkan suatu sumber informasi yang akurat, tepat guna juga efektif dan efisien dalam menjalankan manajemen pemasaran sesuai dengan perkembangan teknologi. Metode penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif. Fokus penelitian ini adalah untuk memahami gambaran sistem informasi pemasaran berbasis web dan memahami gambaran sistem informasi pemasaran berbasis web dalam mendukung manajemen pemasaran yang diterapkan pada CV. Karya Gaja Mandiri. Sistem informasi pemasaran menjadi hal yang sangat penting bagi perusahaan dalam menyelesaikan masalah-masalah pemasaran dan menganalisa cara perusahaan untuk bersaing dengan para kompetitor, sehingga perusahaan tersebut dapat bertahan hidup dalam persaingan bisnis. Hasil penelitian ini menunjukkan beberapa cara dalam memasarkan produk melalui media online dengan menggunakan strategi SEO (Search Engine Optimization) dalam menarik pengunjung media online dan penggunaan DSS (Decision Support Systems) dalam merancang strategi pemasaran agar kegiatan pemasaran dapat berjalan secara efektif dan efisien. Kata Kunci: Sistem Informasi Pemasaran, Manajemen Pemasaran, Website